CONTEMPORARY INTERPRETATION METHODOLOGY: A COMPARATIVE STUDY OF THE THOUGHT OF FAZLUR RAHMAN AND SAHIRON SYAMSUDDIN - Faizal, Muhammad; Melyasari, Eliza (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
This study examines the Methodology of Contemporary Interpretation by comparing the thoughts of Fazlur Rahman and Sahiron Syamsuddin. The background of this study is related to the phenomenon of contemporary interpretation that is developing in today's society. The goal is to explain the differences and similarities between the two figures. The research uses the library research method, by analyzing data from various literature sources. The discussion is carried out in a descriptive manner, namely by describing the findings from relevant literature sources before further analysis. The sources used are mostly secondary literature supplemented with additional references. The results of the study show that Fazlur Rahman, through  the Double Movement methodology, offers a progressive approach to understanding the Qur'an with two stages: first, exploring the historical context when revelation was revealed; second, adapting these values into contemporary reality. On the other hand, Sahiron Syamsuddin developed  the Ma'na cum Maghza method  which emphasizes the exploration of the literal meaning (ma'na) and the main message (maghza) of the text, as well as its application in the contemporary context. These two methods have similarities in the use of hermeneutics to interpret the Qur'an in a relevant way to modern social conditions, but differ in their scope and emphasis. Rahman's Double Movement is more focused on legal verses, while Ma'na cum Maghza Sahiron can be applied to all types of verses except al-huruf al-muqatta'a. Another difference lies in Sahiron's attention to the importance of literal and historical meaning, which Rahman considered less emphasized.